2019
DOI: 10.1002/clc.23147
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2‐VASc score predicts atrial fibrillation recurrence after cardioversion: Systematic review and individual patient pooled meta‐analysis

Abstract: Background Despite progresses in the treatment of the thromboembolic risk related to atrial fibrillation (AF), the management of recurrences remains a challenge. Hypothesis To assess if congestive heart failure or left ventricular systolic dysfunction (CHA 2 DS 2 ‐VASc) score is predictive of early arrhythmia recurrence after AF cardioversion. Methods Systematic review and individual patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
3
18
0
1
Order By: Relevance
“…Patients with pre-existing AF admitted for critical illness have a baseline thromboembolic risk which could be further raised by other factors related to the coexistent acute pathology, its treatment, organ dysfunctions and systemic inflammation 35 . CHA 2 DS 2 -VASc is a generic marker of risk, proven to be useful in several settings different from its original scope 36 . However, it is not validated for the critical illness, where it could be representative of the subject’s baseline risk, not considering the factors associated with the critical care environment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pre-existing AF admitted for critical illness have a baseline thromboembolic risk which could be further raised by other factors related to the coexistent acute pathology, its treatment, organ dysfunctions and systemic inflammation 35 . CHA 2 DS 2 -VASc is a generic marker of risk, proven to be useful in several settings different from its original scope 36 . However, it is not validated for the critical illness, where it could be representative of the subject’s baseline risk, not considering the factors associated with the critical care environment.…”
Section: Discussionmentioning
confidence: 99%
“…CHA 2 DS 2 -VASc is a simple, clinical risk factor-based approach to thromboprophylaxis. Although the CHA2DS 2 -VASc score has been widely used to evaluate the risk recurrence of AF [7] and ischemic stroke in patients with AF [8], there has been limited evidence of LAT/LASEC prediction according to CHA2DS2-VASc scores. In 2015, a letter to an editor [9] reported that a high CHA 2 DS 2 -VASc score can predict LAT/LASEC by analyzing six relevant studies [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…high-risk AF, defined by CHA 2 DS 2 -VASc score 2 or higher for men and 3 or higher for women, according to the 2016 ESC Guidelines (Kirchhof et al, 2016), for included patients to be in more equivalent positions, adapting a factor predictive of being more susceptible to AF recurrence (Falsetti et al, 2014;Vitali et al, 2019) corresponding to the guidelines;…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is not only the use of antiarrhythmic medications that has an impact on sinus rhythm maintenance. For instance, it has been established that CHA 2 DS 2 -VASc score values of at least 2 are predictive of early AF recurrence after ECV (Falsetti et al, 2014;Vitali et al, 2019), suggesting that AF recurrence prevention in high-risk patients is more challenging.…”
Section: Introductionmentioning
confidence: 99%